How peer mechanism impacts loan repayment in a Self-help group?: An empirical study in India - Nishi Malhotra (PLoS ONE, 2026)
Women’s empowerment through financial inclusion is an important sustainable development goal. Formal institutions and banks are hesitant to lend to the poor due to the lack of collateral and information asymmetry. The self-help groups address this gap through a social contract based on social capital and joint liability. The joint liability gives rise to a peer mechanism in the form of peer selection, monitoring and peer sanctions. This study examines how peer group in West Bengal, India, using data from 400 members and ordered logistic regression. As per the findings, peer selection reduces adverse selection, and peer monitoring mitigates moral hazard among the members of the group. Further leadership and access to technology strengthen the repayment behaviour. However, excessive peer sanctions can lead to increased misuse of funds. The study aims to highlight the potential limitations of the peer mechanism in reducing information asymmetry and increasing repayment of loans with policy implications.